2017
DOI: 10.1016/j.joule.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Modulated Tin Sites Enable Highly Selective Electrochemical Reduction of CO2 to Formate

Abstract: The electrochemical reduction of carbon dioxide (CO 2 RR) offers a compelling route to energy storage and high-value chemical manufacture. The presence of sulfur atoms in catalyst surfaces promotes undercoordinated sites, thereby improving the electrochemical reduction of CO 2 to formate. The resulting sulfurmodulated tin catalysts accelerate CO 2 RR at geometric current densities of 55 mA cm À2 at À0.75 V versus RHE with a Faradaic efficiency of 93%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
283
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 429 publications
(306 citation statements)
references
References 47 publications
(81 reference statements)
8
283
1
1
Order By: Relevance
“…It achieved the maximum formate Faradaic efficiency of ≈85% and current density of ≈14 mA cm −2 at η = 680 mV in 0.5 m NaHCO 3 . In a parallel study, Sargent and co‐workers deposited SnS x on Au nanoneedles via atomic layered deposition, then electrochemically reduced it to partially remove the sulfur species and obtained the sulfur‐modulated tin (Sn(S)) catalyst for CO 2 RR ( Figure 7 a,b) . The authors suggested that the presence of remaining sulfur atoms at the surface promoted undercoordinated sites, and favored the selective electrochemical reduction of CO 2 to formate as supported by density functional theory (DFT) calculations.…”
Section: Main Group Metal–based Electrocatalysts For Selective Co2rr mentioning
confidence: 91%
“…It achieved the maximum formate Faradaic efficiency of ≈85% and current density of ≈14 mA cm −2 at η = 680 mV in 0.5 m NaHCO 3 . In a parallel study, Sargent and co‐workers deposited SnS x on Au nanoneedles via atomic layered deposition, then electrochemically reduced it to partially remove the sulfur species and obtained the sulfur‐modulated tin (Sn(S)) catalyst for CO 2 RR ( Figure 7 a,b) . The authors suggested that the presence of remaining sulfur atoms at the surface promoted undercoordinated sites, and favored the selective electrochemical reduction of CO 2 to formate as supported by density functional theory (DFT) calculations.…”
Section: Main Group Metal–based Electrocatalysts For Selective Co2rr mentioning
confidence: 91%
“…Furthermore, high-curvature structures, such as nanoneedles, promote nucleation of smaller gas bubbles 27 , and benefit from field-induced reagent concentration [28][29][30][31][32] , where high local negative electric fields concentrate positively charged cations to help stabilize CO 2 reduction intermediates 33 , enhancing CO 2 RR. However, combining high-curvature morphology with Cu + promotion to enable selective chemical conversion has yet to be explored.…”
Section: Articlesmentioning
confidence: 99%
“…For instance, Bi nanosheets catalyst that are generated from atomic‐thick Bi oxycarbonate nanosheets display a FE HCOO − of ≈100% at −0.9 V and this activity is partly attributed to the presence of Bi(101) and Bi(111) facets, which are demonstrated to lower free energy barrier for formation of *OCHO radical, facilitating CO 2 RR . Similar facet dependent DFT results with Sn, In and Bi catalysts were used as theoretical evidence to justify the catalytic activity of these catalysts for CO 2 RR . In addition, SnO 2 (110) is reported to play a positive role in dictating formate generation during CO 2 RR with a number of literatures with SnO 2 nanoparticle catalysts ascribing the importance of this facet …”
Section: Active Sites In Metal‐based Catalystsmentioning
confidence: 86%